Muscle strength analysis of elbow and knee joints of freestyle wrestlers in china - Dong, D.; Liu, W.; Zhuo, S.U.N.; Xuanchong, X. U. (Journal of Capital University of Physical Education and Sports, 2015)
Through the ISOMED 2000 muscle testing system,the flexion and extension motion of the el-bow and knee joints of male freestule wrestling athletes (12 master wrestlers,9 excellent wrestlers and 15 ordinary wrestlers) are analized.The results show that 1 ) the extensor is better than flexor muscle strength for freestile wrestlers (<0.05);2)there are significant differences between athletes of different levels with PT/BW0°/s ,APT/BW0°/s ,AP180°/s ,WF180°/s ,H/Q0°/s and other muscle strength index (<0.05,<0.01,<0.001);3)most index of elbow joint flexion and extension muscles are within a rea-sonable range,with the stabilitu of knee joint in the fast state(180°/s)being easy to be broken.It can be concluded that:1)elbow muscles of freestyle wrestlers may need to develop fast strength on the basis of maximum force;2 )elbow muscles of freestule wrestlers need to develop fast strength,and stabilitu strength training in the fast-moving state is a keu in the future;3)the maximum strength of both elbow joint and knee joint shows a significant correlation in between low-level athletes,while,with the improvement of the activity level,speed strength shows more significant correlation.Meanwhile,the stability muscle strength of the knee joint also exhibits closer relationship with sports level.